Displacing the Psychology of the Individual in Ethical Decision-Making: The Social Constructivism Model - Cottone, R. Rocco (Canadian Journal of Counselling and Psychotherapy, 2007)
A social constructivism model of ethical decision-making is summarized and related to the Canadian Counseling Association Code of Ethics. Social constructivism is described as an intellectual movement that allows for a biological and social conception of human understanding, thereby superceding or displacing psychological theory. The theoretical progression from the "psychology of the individual" to social constructivism is described and is represented by the author's transformation from a psychological to a social theorist. Applications to ethical decisions are provided. Multicultural applications are also explored.